The Problematika Pendampingan Orang Tua pada Anak dalam Proses Belajar di Rumah Masa Pandemi Covid-19 - Faqih Abdul Bashir; Bramastia; Eka Khristiyanta Purnama (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2024)
The role of parents in assisting children to study at home has strengthened again during the Covid-19 pandemic. However, parents experience various obstacles in assisting their children's learning process. The study aimed to discover parents' obstacles when assisting children in learning from home. The data collection method used a survey of students throughout Indonesia. The cluster random sampling technique obtained as many as 46,547 parents online and 602 through Short Message Service (SMS). A sampling of respondents in each province, Frontier, Remote and Disadvantaged (3T region) and non-3T regions. The data analysis in this study used a quantitative descriptive method. The results showed that 42 % of parents had difficulty understanding the learning material, 32% of parents lacked focus in assisting children, 35 % of parents could not interact directly with teachers, 15 % of parents did not have digital devices, 30 % of parents did not have the skills to use digital devices, 30 % of parents constrained by an inadequate internet network, in addition there are 3 % of parents who experience problems with an inadequate electricity network. This study concludes that the problem of parents' assistance to children in the learning process at home during the COVID-19 pandemic is the lack of understanding of children's learning material, lack of access to interaction with teachers, lack of facilities and infrastructure, and lack of ability to master technology.